2017
DOI: 10.1371/journal.pone.0175166
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of curable sexually transmitted infections among pregnant women in a rural county hospital in Kilifi, Kenya

Abstract: BackgroundWomen attending antenatal care (ANC) in resource-limited countries are frequently screened for syphilis and HIV, but rarely for other sexually transmitted infections (STIs). We assessed the prevalence of curable STIs, defined as infection with either Chlamydia trachomatis or Neisseria gonorrhoeae or Trichomonas vaginalis, from July to September 2015.MethodsIn a cross-sectional study, women attending ANC at the Kilifi County Hospital, Kenya, had a urine sample tested for C. trachomatis/N. gonorrhoeae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 46 publications
6
42
5
Order By: Relevance
“…The overall cumulative prevalence of BV in 13 studies conducted in the eastern part of Africa among all pregnant women was about 23.8%, which have the intermediate prevalence of BV in the African region (Table 1), with the highest prevalence of BV was reported from Kenya 52% [17] then followed from Sudan 49.8% [24]. In Ethiopia, the prevalence of BV among all pregnant women (symptomatic and asymptomatic) ranges from 0.5% to 19.4 [25,26] with the cumulative prevalence of 13.8%, whereas in Kenya including HIV infected pregnant women ranges from 19.4-52% [13,17] with the highest cumulative of 29%.…”
Section: East Africamentioning
confidence: 96%
See 4 more Smart Citations
“…The overall cumulative prevalence of BV in 13 studies conducted in the eastern part of Africa among all pregnant women was about 23.8%, which have the intermediate prevalence of BV in the African region (Table 1), with the highest prevalence of BV was reported from Kenya 52% [17] then followed from Sudan 49.8% [24]. In Ethiopia, the prevalence of BV among all pregnant women (symptomatic and asymptomatic) ranges from 0.5% to 19.4 [25,26] with the cumulative prevalence of 13.8%, whereas in Kenya including HIV infected pregnant women ranges from 19.4-52% [13,17] with the highest cumulative of 29%.…”
Section: East Africamentioning
confidence: 96%
“…In Ethiopia, a study conducted in Felegehiwot referral hospital, on Common causes of vaginal infections and antibiotic susceptibility of aerobic bacterial isolates in women of reproductive age(pregnant and nonpregnant), reported that BV was higher among non-pregnant women (11/195, 5.6%) than pregnant women(1/214, 0.5%) and signi cant association was seen in the age group of 40-49 years [25]. [29,37] Marital status 2 [21,29] Multiple LTSP 2 [20,26] Gestational age 1 [32] Residence 1 [25] Number of pregnancy 1 [30] History of abortion 2 [21,26] Preterm delivery 1 [14] Low birth weight 1 [14] premature rupture of membranes 1 [14] Previous BV/STI 3 [13,20,21] Douching 1 [13] Vaginal discharge 2 [29,30] Contraceptive use 1 [23] HIV 6 [11,17,27,32,36,38] [31] .…”
Section: Agementioning
confidence: 99%
See 3 more Smart Citations